FEATURES OF ANXIETY CORRECTION IN CHILDREN BY ART THERAPY - Дацун, Олена (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2025)
The article considers one of the actual scientific and practical problems of modern psychological science – overcoming anxiety in children by art therapy. For effectively self-realization in life, increased motivation for learning and the best show children’s social skills, it is necessary to reduce the level of their anxiety. Therefore, it is important to pay attention to the development of an anxiety methods of correction of situational anxiety in children during military conflicts. Art therapy is effective method of psychological correction, which allows the child to express himself safety through creative (drawing, dance, applique, music, ect.). The purpose of the study: to develop a comprehensive program for the correction of anxiety in children by means of art therapy. The following research methods were used to solve the set tasks: analysis of scientific literature; logical-structural modeling for the development of a correctional program anxiety in children; analysis of products of activity of students at performance of the developed individual tasks. Results: based on the theoretical analysis of the scientific literature the peculiarities of the manifestation of anxiety for children. Anxiety diagnosis was performed using of a projective test «Family»; the method of monitoring emotional states in children; Methods for diagnosing the emotional state of children in lessons. For correction anxiety, the comprehensive program has been developed using art-therapeutic techniques: in particular, the method of dating «Tell us about your name», «Collage of random words», «My magic island», «Working with salt. Drawing a butterfly». The stages of correctional work and the principles of construction of a safe therapeutic environment for working with children are given. Conclusions: Art therapy is a safe method of helping children with high anxiety. The proposed art therapeutic methods can be recommended for the development of anxiety correction programs in children.